Magnitude of Symptomatic Pelvic Floor Dysfunction and Associated Factors Amongst Women in Western Ethiopia: A Cross-Sectional Study - Hunduma Dina Hambisa MSc; Zelalem Birku MSc; Samuel Gedamu MSc (Inquiry: The Journal of Health Care Organization, Provision, and Financing, 2023)
The goal of this research was to determine the extent of pelvic floor dysfunction and the factors that contribute to it. The study design was community-focused and cross-sectional, and participants were chosen using a systematic random sampling technique. For data entry and cleansing, we used EPI data version 3.1 software, and for analysis, we used Statistical Package for the Social Sciences version 26. The 95% confidence interval was predicted, and the factor with a significant level less than 0.05 was chosen for multivariate logistic regression analysis. The overall Magnitude of pelvic floor dysfunction was 37.7% [(95% confidence interval (31.7-42.5)]. The most common type of pelvic floor dysfunction is overactive bladder, which was reported by 135 of all participants. Pelvic organ prolapse accounted for 92 (30.4%) of all cases, and 4 factors were found to be significantly associated with pelvic floor dysfunction. In this study, age 55 years [(AOR = 2.1; 95% CI: (1.52-6.42)], heavy labor work for more than 10 years [(AOR = 3.21; 95% CI: (1.86-5.72) grand-multipara, and being menopause [(AOR = 4.03; 95% CI: (2.20-8.27)] were linked to symptoms of pelvic floor dysfunction. The magnitude of pelvic floor dysfunction in this study was slightly higher than in Ethiopian studies. Pelvic floor dysfunction has been linked to heavy load lifting, low socioeconomic status, recurrent vaginal deliveries, chronic cough, and menopause. Screening and treatment of pelvic floor disorders should be prioritized in collaboration with regional and zonal health departments.